Research on police physical training based on virtual reality technology - Du, Yang (Quality in Sport, 2025)
With the acceleration of science and technology innovation, Virtual Reality technology (VR) has been widely used in many fields. At the level of police physical training, VR provides technical support for the innovation of traditional training mode by virtue of the characteristics of environmental simulation, process controllability and risk avoidance. This study focuses on the practical application of VR technology in police physical training, and systematically demonstrates its technical adaptability, implementation path and optimization direction. Analyze its technical advantages, specific application methods, as well as the problems and challenges faced in this field. The research shows that the technology can effectively simulate the actual combat environment, promote the coordinated development of the stress response and psychological adjustment ability of the trainees, and reduce the equipment loss and time cost, which has important practical value in promoting the modernization of the police training system.